Humanitarian intervention: legality, legitimacy and the search for solutions - Babatunde, Elkanah Oluwapelumi (Department of Public Law, 2017)
Humanitarian intervention refers to the use of force for the protection of human rights in a foreign state and usually against the will of the state in which force is used. The legality of unilateral humanitarian Intervention is a widely contested area in contemporary international law. It is a discussion that cuts across law, morality and foreign policy. Humanitarian intervention brings to the fore the contention between the principles of sovereignty and political independence on one hand and human rights and the principle of common humanity on the other hand. Some scholars contend that humanitarian intervention is a violation of the principles of sovereignty and political independence of states and violates Article 2(4) of the United Nations (UN) Charter. Other scholars have argued that Artcicle 2(4) of the UN Charter does not prohibit the use of force for human rights purposes but rather prohibits use of force which is targeted against a state's political framework or territorial annexation. They argue further that huamn rights constitutes one of the purposes of the UN and it is therefore unthinkable that the UN Charter will prohibit the use of force for such a purpose as human rights. Humanitarian intervention thus stands at the crossroasds of very foundational principle of both customary international law and the UN Charter. In this thesis, I argue that humanitarian intervention is illegal under the UN Charter as it does not fall within the two exceptions to the use of force: self-defence and Security Council sanctioned use of force. However, I go further to argue for the legitimacy of humanitarian intervention based on the principles of common humanity and wider principles of sovereignty. This argument draws from the just war doctrine as postulated by Grotius and other early just war theorists. The need to allow for unilateral intervention is pertinent given the rise in the abuse of power by some governments. Sovereignty should not be an umbrella that shields human rights abuses.